Preparation process of high-toughness modified PC / ABS composite material
By adding modified bile acid, carbon nanotube modified imidazole and other components to the preparation process of highly tough modified PC/ABS composite materials, a cross-linking network and an antibacterial system is formed, which solves the problem of insufficient antibacterial performance of existing materials and realizes the realization of the realization of the antibacterial performance of existing materials. The material has good tensile properties and significant antibacterial effects.
Patent Information
- Application Number
- CN202411787436.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing highly tough modified PC/ABS composites have shortcomings in antibacterial properties, which limits their application scope.
By adding modified bile acid, carbon nanotube modified imidazole, epoxy nanosilica and other components to the preparation process, and blending them through a twin-screw extruder, a cross-linking network and an antibacterial system are formed to improve the antibacterial performance of the material.
The high-toughness modified PC/ABS composite material has achieved good tensile performance and significantly improved antibacterial effect, expanding its application range.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a preparation process of a high-toughness modified PC / ABS composite material. Background Art
[0002] With the continuous development of industrial manufacturing, the application fields of engineering plastics are becoming more and more extensive, and engineering plastics in different fields need to have different properties. Polycarbonate PC is a tough thermoplastic engineering material with excellent mechanical properties; ABS has excellent mechanical properties, dimensional stability, processability, and chemical resistance, but the antibacterial properties of both have not been improved, which greatly limits their application scope.
[0003] For example, patent CN10684335A discloses a preparation process of a high-toughness modified PC / ABS composite material, which has excellent impact resistance and fluidity, and will not precipitate after long-term storage to affect the feel; however, its antibacterial properties are not improved. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the deficiencies of the prior art, the present invention provides a preparation process of a high-toughness modified PC / ABS composite material with good tensile properties and antibacterial properties.
[0006] (II) Technical solution
[0007] To achieve the above object, the present invention provides the following technical solution: a preparation process of a high-toughness modified PC / ABS composite material, wherein the preparation process of the high-toughness modified PC / ABS composite material is:
[0008] (1) adding chitosan to an acetic acid solvent, stirring to dissolve, adding a mixed solution of thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent thereto, adjusting the pH to 4-6, reacting at 80-95° C. for 7-15 hours, filtering, washing and drying after the reaction to obtain an intermediate 1;
[0009] (2) adding bile acid to a reactor containing a dimethylformamide solvent, and continuing to add tri(2-aminoethyl)amine after dissolution, and adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride under an ice bath, stirring and dissolving, and activating for 8-15 minutes, and continuing to add 1-hydroxybenzotriazole catalyst, stirring and reacting at room temperature for 20-24 hours, and precipitating in a sodium bicarbonate aqueous solution after the reaction, and then washing to obtain a bile acid trimer;
[0010] (3) adding the bile acid trimer and 6-chloro-1-hexene to a flask containing acetonitrile solvent, stirring and dispersing, heating to 70-90° C., reacting for 12-14 hours, and after the reaction is completed, removing the solvent by rotary distillation, filtering, and drying to obtain quaternary ammonium salt-modified olefinic bile acid;
[0011] (4) adding intermediate 1, quaternary ammonium salt-modified olefinic cholic acid and benzoin dimethyl ether photoinitiator to N,N-dimethylformamide solvent, irradiating with 365 nm ultraviolet light at 45-60° C. for 3-5 h, centrifuging, washing and drying to obtain modified cholic acid;
[0012] (5) Under a nitrogen atmosphere, 3-5 parts by weight of 1-vinylimidazole, 2-4 parts by weight of vinyl carbon nanotubes, 1-3 parts by weight of quaternary ammonium salt-modified olefinic cholic acid, and 1-2 parts by weight of allyl alcohol are added to N,N-dimethylformamide solvent, stirred evenly, and then 0.02-0.03 parts by weight of azobisisobutyronitrile initiator is added thereto, and the reaction is carried out at 90-105° C. After the reaction is completed, the solvent is removed by distillation under reduced pressure, washed, and dried to obtain carbon nanotube-modified imidazole;
[0013] (6) 80-100 parts by weight of acrylonitrile-butadiene-styrene copolymer, 70-95 parts by weight of polycarbonate, 4-10 parts by weight of modified bile acid, 5-12 parts by weight of epoxy nano-silica, and 3-6 parts by weight of carbon nanotube-modified imidazole are added into a twin-screw extruder, blended, and extruded to obtain a modified PC / ABS composite material with high toughness.
[0014] Preferably, the mass ratio of chitosan, thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent in (1) is 1:2.4-2.6:0.02-0.05.
[0015] Preferably, the mass ratio of cholic acid, tris(2-aminoethyl)amine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-hydroxybenzotriazole catalyst in (2) is 1:2.1-2.4:0.01-0.02:0.01-0.015.
[0016] Preferably, the mass ratio of bile acid trimer to 6-chloro-1-hexene in (3) is 1:1.4-1.6.
[0017] Preferably, the mass ratio of the intermediate 1, the quaternary ammonium salt-modified olefinic cholic acid, and the benzoin dimethyl ether photoinitiator in (4) is 1.1-1.3:1:0.02-0.03.
[0018] Preferably, the reaction time in (5) is 10-14 h.
[0019] Preferably, the blending temperature in (6) is 180-190°C.
[0020] Preferably, the extrusion temperature in (6) is 170-180°C.
[0021] (III) Beneficial technical effects
[0022] The invention obtains a modified PC / ABS composite material with high toughness by adding acrylonitrile-butadiene-styrene copolymer, polycarbonate, modified bile acid, epoxy nano-silicon dioxide and carbon nanotube modified imidazole into a twin-screw extruder, blending and extruding.
[0023] During the extrusion process, the hydroxyl groups in the modified bile acid and carbon nanotube-modified imidazole will undergo a ring-opening reaction with epoxy nano-silica to form organic-inorganic hybrid particles, which will further entangle with acrylonitrile-butadiene-styrene copolymer and polycarbonate to form a cross-linked network with more force fulcrums, thereby improving its tensile properties and having better toughness, and the carbon nanotubes themselves have good tensile effects; the quaternary ammonium salt groups, imidazole groups, and sulfur elements in the modified bile acid and carbon nanotube-modified imidazole all have good antibacterial effects and together constitute an antibacterial system, and chitosan itself has good antibacterial properties; the bile acid trimer reacts with 6-chloro-1-hexene to increase the degree of substitution of the olefin group, and then reacts with the intermediate 1 to introduce more sulfur elements, further improving its antibacterial effect. DETAILED DESCRIPTION
[0024] Example 1
[0025] (1) adding chitosan to an acetic acid solvent, stirring to dissolve, adding a mixed solution of thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent thereto, wherein the mass ratio of chitosan, thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent is 1:2.4:0.02, adjusting the pH to 4, reacting at 80° C. for 7 h, filtering, washing and drying after the reaction is completed to obtain an intermediate 1;
[0026] (2) adding cholic acid to a reactor containing a dimethylformamide solvent, and continuing to add tri(2-aminoethyl)amine after dissolution, and adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride under an ice bath, stirring and dissolving, and activating for 8 minutes, and continuing to add 1-hydroxybenzotriazole catalyst, wherein the mass ratio of cholic acid, tri(2-aminoethyl)amine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-hydroxybenzotriazole catalyst is 1:2.1:0.01:0.01, stirring and reacting at room temperature for 20 hours, and precipitating in a sodium bicarbonate aqueous solution after the reaction, and then washing to obtain a cholic acid trimer;
[0027] (3) adding bile acid trimer and 6-chloro-1-hexene to a flask containing acetonitrile solvent, wherein the mass ratio of bile acid trimer to 6-chloro-1-hexene is 1:1.4-1.6, stirring and dispersing, heating to 70° C., reacting for 12 hours, and after the reaction is completed, removing the solvent by rotary distillation, filtering, and drying to obtain quaternary ammonium salt-modified olefinic bile acid;
[0028] (4) adding intermediate 1, quaternary ammonium salt modified olefinic cholic acid and benzoin dimethyl ether photoinitiator to N,N-dimethylformamide solvent, wherein the mass ratio of intermediate 1, quaternary ammonium salt modified olefinic cholic acid and benzoin dimethyl ether photoinitiator is 1.1:1:0.02, irradiating with 365 nm ultraviolet light at 45° C. for 3 h, centrifuging after irradiation, washing and drying to obtain modified cholic acid;
[0029] (5) Under a nitrogen atmosphere, 3 parts by weight of 1-vinyl imidazole, 2 parts by weight of vinyl carbon nanotubes, 1 part by weight of quaternary ammonium salt-modified olefinic cholic acid, and 1 part by weight of allyl alcohol are added to N,N-dimethylformamide solvent, stirred evenly, and 0.02 parts by weight of azobisisobutyronitrile initiator is added thereto, and the reaction is carried out at 90° C. for 10 hours. After the reaction, the solvent is removed by reduced pressure distillation, washed, and dried to obtain carbon nanotube-modified imidazole;
[0030] (6) 80 parts by weight of acrylonitrile-butadiene-styrene copolymer, 70 parts by weight of polycarbonate, 4 parts by weight of modified bile acid, 5 parts by weight of epoxy nano-silica, and 3 parts by weight of carbon nanotube-modified imidazole are added to a twin-screw extruder at a blending temperature of 180° C. and an extrusion temperature of 170° C. to obtain a modified PC / ABS composite material with high toughness.
[0031] Example 2
[0032] (1) adding chitosan to an acetic acid solvent, stirring to dissolve, adding a mixed solution of thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent thereto, wherein the mass ratio of chitosan, thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent is 1:2.6:0.05, adjusting the pH to 6, reacting at 95° C. for 15 h, filtering, washing and drying after the reaction to obtain an intermediate 1;
[0033] (2) adding cholic acid to a reactor containing a dimethylformamide solvent, and continuing to add tri(2-aminoethyl)amine after dissolution, and adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride under an ice bath, stirring and dissolving, and activating for 15 minutes, and continuing to add 1-hydroxybenzotriazole catalyst, wherein the mass ratio of cholic acid, tri(2-aminoethyl)amine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-hydroxybenzotriazole catalyst is 1:2.4:0.02:0.015, stirring and reacting at room temperature for 24 hours, and precipitating in a sodium bicarbonate aqueous solution after the reaction, and then washing to obtain a cholic acid trimer;
[0034] (3) adding bile acid trimer and 6-chloro-1-hexene to a flask containing acetonitrile solvent, wherein the mass ratio of bile acid trimer to 6-chloro-1-hexene is 1:1.6, stirring and dispersing, heating to 90° C., reacting for 14 hours, and after the reaction is completed, removing the solvent by rotary distillation, filtering, and drying to obtain quaternary ammonium salt-modified olefinic bile acid;
[0035] (4) adding intermediate 1, quaternary ammonium salt modified olefinic cholic acid and benzoin dimethyl ether photoinitiator to N,N-dimethylformamide solvent, wherein the mass ratio of intermediate 1, quaternary ammonium salt modified olefinic cholic acid and benzoin dimethyl ether photoinitiator is 1.3:1:0.03, irradiating with 365 nm ultraviolet light at 60° C. for 5 h, centrifuging after irradiation, washing and drying to obtain modified cholic acid;
[0036] (5) Under a nitrogen atmosphere, 5 parts by weight of 1-vinyl imidazole, 4 parts by weight of vinyl carbon nanotubes, 3 parts by weight of quaternary ammonium salt-modified olefinic cholic acid, and 2 parts by weight of allyl alcohol are added to N,N-dimethylformamide solvent, stirred evenly, and 0.03 parts by weight of azobisisobutyronitrile initiator is added thereto, and the reaction is carried out at 105° C. for 14 hours. After the reaction, the solvent is removed by reduced pressure distillation, washed, and dried to obtain carbon nanotube-modified imidazole;
[0037] (6) 100 parts by weight of acrylonitrile-butadiene-styrene copolymer, 95 parts by weight of polycarbonate, 10 parts by weight of modified bile acid, 12 parts by weight of epoxy nano-silica, and 6 parts by weight of carbon nanotube-modified imidazole are added into a twin-screw extruder at a blending temperature of 190° C. and an extrusion temperature of 180° C. to obtain a modified PC / ABS composite material with high toughness.
[0038] Example 3
[0039] (1) adding chitosan to an acetic acid solvent, stirring to dissolve, adding a mixed solution of thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent thereto, wherein the mass ratio of chitosan, thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent is 1:2.5:0.035, adjusting the pH to 5, reacting at 90° C. for 12 h, filtering, washing and drying after the reaction is completed to obtain an intermediate 1;
[0040] (2) adding cholic acid to a reactor containing a dimethylformamide solvent, and continuing to add tri(2-aminoethyl)amine after dissolution, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride under an ice bath, stirring and dissolving, activating for 8-15 minutes, and continuing to add 1-hydroxybenzotriazole catalyst, wherein the mass ratio of cholic acid, tri(2-aminoethyl)amine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-hydroxybenzotriazole catalyst is 1:2.3:0.015:0.012, stirring and reacting at room temperature for 22 hours, precipitating in a sodium bicarbonate aqueous solution after the reaction, and then washing to obtain a cholic acid trimer;
[0041] (3) adding bile acid trimer and 6-chloro-1-hexene to a flask containing acetonitrile solvent, wherein the mass ratio of bile acid trimer to 6-chloro-1-hexene is 1:1.5, stirring and dispersing, heating to 80° C., reacting for 13 hours, and after the reaction is completed, removing the solvent by rotary distillation, filtering, and drying to obtain quaternary ammonium salt-modified olefinic bile acid;
[0042] (4) adding intermediate 1, quaternary ammonium salt modified olefinic cholic acid and benzoin dimethyl ether photoinitiator to N,N-dimethylformamide solvent, wherein the mass ratio of intermediate 1, quaternary ammonium salt modified olefinic cholic acid and benzoin dimethyl ether photoinitiator is 1.2:1:0.025, irradiating with 365 nm ultraviolet light at 55° C. for 4 h, centrifuging after irradiation, washing and drying to obtain modified cholic acid;
[0043] (5) Under a nitrogen atmosphere, 4 parts by weight of 1-vinyl imidazole, 3 parts by weight of vinyl carbon nanotubes, 2 parts by weight of quaternary ammonium salt-modified olefinic cholic acid, and 1.5 parts by weight of allyl alcohol are added to N,N-dimethylformamide solvent, stirred evenly, and 0.025 parts by weight of azobisisobutyronitrile initiator is added thereto, and the reaction is carried out at 100° C. for 12 hours. After the reaction, the solvent is removed by reduced pressure distillation, washed, and dried to obtain carbon nanotube-modified imidazole;
[0044] (6) 90 parts by weight of acrylonitrile-butadiene-styrene copolymer, 82 parts by weight of polycarbonate, 7 parts by weight of modified bile acid, 8 parts by weight of epoxy nano-silica, and 4 parts by weight of carbon nanotube-modified imidazole are added to a twin-screw extruder at a blending temperature of 185° C. and an extrusion temperature of 175° C. to obtain a modified PC / ABS composite material with high toughness.
[0045] Comparative Example 1
[0046] 90 parts by weight of acrylonitrile-butadiene-styrene copolymer, 82 parts by weight of polycarbonate, 8 parts by weight of epoxy nano-silica, and 4 parts by weight of carbon nanotube-modified imidazole are added to a twin-screw extruder with a blending temperature of 185°C and an extrusion temperature of 175°C to obtain a modified PC / ABS composite material with high toughness.
[0047] Comparative Example 2
[0048] 90 parts by weight of acrylonitrile-butadiene-styrene copolymer, 82 parts by weight of polycarbonate, 7 parts by weight of modified bile acid, and 8 parts by weight of epoxy nano-silica are added to a twin-screw extruder with a blending temperature of 185°C and an extrusion temperature of 175°C to obtain a modified PC / ABS composite material with high toughness.
[0049] A Staphylococcus aureus liquid with a concentration of 2×108 CFU / mL was added to a sterilized culture dish as a test strain, and then a solid agar medium was added and melted, cooled to 45°C, and then poured into the culture dish, 20 mL was poured into each plate with an inner diameter of 10 cm, and then the antibacterial materials of the embodiments of the present invention and the comparative example (with a diameter of 3 cm and a thickness of 1 mm) were placed on the culture plate, and cultured in a constant temperature incubator for 12 hours at a temperature of 37°C. After culture, the diameter of the inhibition zone was measured. The test results are shown in Table 1.
[0050] Table 1: Antimicrobial testing.
[0051] project Diameter of inhibition zone (mm) Example 1 16.9 Example 2 17.3 Example 3 16.2 Comparative Example 1 11.4 Comparative Example 2 12.1
[0052] As can be seen from Table 1, the high-toughness modified PC / ABS composite materials of the present invention, Examples 1-3 have larger inhibition zones than Comparative Examples 1-2, indicating better antibacterial effects.
[0053] The tensile properties of the material were tested using an electronic universal testing machine. The test results are shown in Table 2.
[0054] Table 2: Tensile properties tested.
[0055] project Tensile properties (MPa) Example 1 41.2 Example 2 43.7 Example 3 42.6 Comparative Example 1 20.5 Comparative Example 2 21.6
[0056] As can be seen from Table 2, the tensile properties of the modified PC / ABS composite materials with high toughness of the present invention are higher in Examples 1-3 than in Comparative Examples 1-2, indicating that they have better tensile properties and therefore better mechanical properties.
[0057] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for preparing a high-toughness modified PC / ABS composite material, characterized in that: The preparation process of the modified PC / ABS composite material with high toughness is as follows: (1) adding chitosan to an acetic acid solvent, stirring to dissolve, adding a mixed solution of thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent thereto, adjusting the pH to 4-6, reacting at 80-95° C. for 7-15 hours, filtering, washing and drying after the reaction to obtain an intermediate 1; (2) adding bile acid to a reactor containing a dimethylformamide solvent, and continuing to add tri(2-aminoethyl)amine after dissolution, and adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride under an ice bath, stirring and dissolving, and activating for 8-15 minutes, and continuing to add 1-hydroxybenzotriazole catalyst, stirring and reacting at room temperature for 20-24 hours, and precipitating in a sodium bicarbonate aqueous solution after the reaction, and then washing to obtain a bile acid trimer; (3) adding the bile acid trimer and 6-chloro-1-hexene to a flask containing acetonitrile solvent, stirring and dispersing, heating to 70-90° C., reacting for 12-14 hours, and after the reaction is completed, removing the solvent by rotary distillation, filtering, and drying to obtain quaternary ammonium salt-modified olefinic bile acid; (4) adding intermediate 1, quaternary ammonium salt-modified olefinic cholic acid and benzoin dimethyl ether photoinitiator to N,N-dimethylformamide solvent, irradiating with 365 nm ultraviolet light at 45-60° C. for 3-5 h, centrifuging, washing and drying to obtain modified cholic acid; (5) Under a nitrogen atmosphere, 3-5 parts by weight of 1-vinylimidazole, 2-4 parts by weight of vinyl carbon nanotubes, 1-3 parts by weight of quaternary ammonium salt-modified olefinic cholic acid, and 1-2 parts by weight of allyl alcohol are added to N,N-dimethylformamide solvent, stirred evenly, and then 0.02-0.03 parts by weight of azobisisobutyronitrile initiator is added thereto, and the reaction is carried out at 90-105° C. After the reaction is completed, the solvent is removed by distillation under reduced pressure, washed, and dried to obtain carbon nanotube-modified imidazole; (6) 80-100 parts by weight of acrylonitrile-butadiene-styrene copolymer, 70-95 parts by weight of polycarbonate, 4-10 parts by weight of modified bile acid, 5-12 parts by weight of epoxy nano-silica, and 3-6 parts by weight of carbon nanotube-modified imidazole are added into a twin-screw extruder, blended, and extruded to obtain a modified PC / ABS composite material with high toughness.
2. The preparation process of the modified PC / ABS composite material with high toughness according to claim 1, characterized in that: The mass ratio of chitosan, thioglycolic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide condensation agent in (1) is 1:2.4-2.6:0.02-0.
05.
3. The preparation process of the high-toughness modified PC / ABS composite material according to claim 1, characterized in that: The mass ratio of bile acid, tris(2-aminoethyl)amine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1-hydroxybenzotriazole catalyst in (2) is 1:2.1-2.4:0.01-0.02:0.01-0.
015.
4. The preparation process of the modified PC / ABS composite material with high toughness according to claim 1, characterized in that: The mass ratio of bile acid trimer to 6-chloro-1-hexene in (3) is 1:1.4-1.
6.
5. The preparation process of the modified PC / ABS composite material with high toughness according to claim 1, characterized in that: The mass ratio of the intermediate 1, quaternary ammonium salt-modified olefinic cholic acid, and benzoin dimethyl ether photoinitiator in the (4) is 1.1-1.3:1:0.02-0.
03.
6. The preparation process of the modified PC / ABS composite material with high toughness according to claim 1, characterized in that: The reaction time in (5) is 10-14h.
7. The preparation process of the high-toughness modified PC / ABS composite material according to claim 1, characterized in that: The blending temperature in the step (6) is 180-190°C.
8. The preparation process of the modified PC / ABS composite material with high toughness according to claim 1, characterized in that: The extrusion temperature in (6) is 170-180°C.